THE EFFECT OF USING SCRAMBLE PARAGRAPH METHOD ON STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT OF THE EIGTH GRADE STUDNET OF SMP NEGERI 2 SATU ATAP BATANG SERANGAN IN ACADEMIC YEAR 2019/2020 - Megawati -; Conny - (Jurnal Serunai Bahasa Inggris, 2020)
The objective of the study was: “to find out whether there is any effect of using scramble paragraph method  on students’ ability in writing procedure text of the eigth grade studnet of SMP Negeri 2 Satu Atap Batang Serangan in academic year 2019/2020”. This research was  conducted at SMP Negeri 2 Satu Atap Jl. Batang Serangan-Kwala Sawit Kecamatan Batang Serangan Kabupaten Langkat. The population of this study was the whole students of eigth Year Students of SMP Negeri 2 Satu Atap Batang Serangan that consist of four class, namely VIII. With the total number of the students were 132 students. Where students of class VIII-2 totaling 32 people as an experimental class and class VIII-4 totaling 32 people as a control group. In this research method was the type of experimental research which is one type of research which aims to provide an overview of the influence of variables x and y variables. The average pretest control class was 56 and the posttest control group rose to 66. While the experimental class average value obtained for 64.7 pretest and posttest riding on the outcome of 76. This shows that the experimental class was better than the control class. Overall the data comes from a normal population and the entire data homogeneous manifold. Of the survey results revealed that to= 12.1 t criticism at 5% level obtained 1.69 and at level 1% obtained t = 1.31 then 1.31 <12.1> 1.69, then the hypothesis of significant meaning hypothesis proved to be true, namely "There is significant affect of using scramble paragraph method  on students ability in writing procedure text of the eigth grade studnet of SMP Negeri 2 Satu Atap Batang Serangan in academic year 2019/2020”.